2020
DOI: 10.3390/app10175981
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adsorbed Volatile Organic Compounds on an Ultrathin Water Film Measurement

Abstract: Using surface plasmon resonance imaging (SPRi), we have recently shown for the first time the existence of a monolayer water film between droplets during dropwise condensation. This study examines the effect of adsorbed volatile organic compounds (VOCs) on the ultrathin film measurement using SPRi. Further, the work presents the proper surface-treatment process that enables measurements of the ultrathin water layer during high-speed imaging of dropwise condensation at 3000 frame per second. In this study, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…It is worth noting that the adsorbed molecules on the surface mostly consist of water molecules and not volatile organic compounds (VOCs). In our previous work [15], we showed that the rate of adsorption of VOCs on the gold surface is much slower than the rate of adsorption of the molecularly adsorbed water layer on the surface. In a different set of experiments, the water bridge on the surface was slightly relocated on the surface by moving the ITO coated glass that is on the top of the water bridge (see Figure 1a).…”
Section: Onset Of Sdcmentioning
confidence: 95%
See 2 more Smart Citations
“…It is worth noting that the adsorbed molecules on the surface mostly consist of water molecules and not volatile organic compounds (VOCs). In our previous work [15], we showed that the rate of adsorption of VOCs on the gold surface is much slower than the rate of adsorption of the molecularly adsorbed water layer on the surface. In a different set of experiments, the water bridge on the surface was slightly relocated on the surface by moving the ITO coated glass that is on the top of the water bridge (see Figure 1a).…”
Section: Onset Of Sdcmentioning
confidence: 95%
“…It is worth noting that the adsorbed molecules on the surface mostly consist of water molecules and not volatile organic compounds (VOCs). In our previous work [15], we showed that the rate of adsorption of VOCs on the gold surface is much slower than the rate of adsorption of the molecularly adsorbed water layer on the surface.…”
Section: Onset Of Sdcmentioning
confidence: 95%
See 1 more Smart Citation
“…The effect of film cooling on the performance of blades is becoming significantly important when the temperature of the gas turbine is raised to enhance its performance [3][4][5]. Computational Fluid Dynamics (CFD) has now found its place among experimental and analytical methods for analyzing fluid flow, heat transfer [6][7][8][9][10][11][12][13], and diverse problems [14][15][16], and the use of this method for engineering analysis has become more common [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the need for visualization of interfacial phenomena with high-frequency features, such as ultrathin film instabilities, we developed an automated SPRi instrument, the first-ever reported instrument capable of imaging a sub-nanometer film at high-speed (up to 10,000 FPS) in ambient conditions [12]. This newly developed near-field imaging system was applied [12][13][14][15] to understand the physics of dropwise condensation, which have been under debate for the past nine decades [4]. We interpret the static dropwise condensation in Umar and Griffith's work [6] as stable dropwise condensation (SDC) occurring at a very low condensation rate, or dropwise condensation that can be sustained on the surface for a long-time.…”
Section: Introductionmentioning
confidence: 99%